ANALISIS PERSEPSI PETANI BAWANG MERAH DALAM PENGGUNAAN PESTISIDA SEBAGAI DASAR PENYUSUNAN POLICY BRIEF DI KABUPATEN BREBES - SRI LESTARI; Hanifa Maher Denny; Yuliani Setyaningsih (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
The improper use of pesticides that are not completely on target causes residues and adversely affects both health and the environment. The lack of knowledge of the dangers of pesticides causes farmers to ignore the risk in excessive use of pesticides. Preventive efforts are needed to reduce the impact of pesticide use. One of them is by organizing policy brief to provide input for the Regional Government regarding the use of pesticides to union farmers.This study uses descriptive analysis with a qualitative approach. Determination of the sample in this study uses purposive sampling technique so that the number of samples obtained by 3 informants. The research sample consisted of onion farmers, cadres of Pos UKK, and Secretary of farmer group.Farmers' perceptions regarding the use of pesticides are influenced by knowledge factors, personal factors, work environment factors, behavioral factors on risks and cultural safety and health factors at work. Many farmers do not pay attention to the risk factors for pesticide exposure, from mixing pesticides that are not in accordance with the dosage, storing pesticides in the open space, eating and drinking immediately after spraying pesticides, not washing hands and bathing after spraying and not using personal protective equipment when doing spraying pesticides. These behaviors can increase the risk of exposure to pesticides which will affect the health of farmers. Farmers' perceptions of the use of pesticides are still not optimal because even though farmers know the impact of inappropriate pesticide use, they still ignore it in its implementation.Keywords : Policy brief, Farmer perceptions, PesticidesÂ